Tuberculosis mortality in El Puerto de Santa María (1923-1926) - Irene López León; J. César Muriel; Ana María Sáinz Otero (Universidad de Alicante, 2014)
The main cause of mortality in El Puerto de Santa María (Cádiz) between 1923 and 1926 was tuberculosis. Our aim is to analyse the tuberculosis mortality rate in this town between 1923 and 1926 and to link it to the principal epidemiological determinants in order to describe the health and sanitary conditions in those years. Descriptive and longitudinal study of the tuberculosis mortality in El Puerto de Santa María between 1923 and 1926. Our information sources were the entries in the register of deaths. A statistical analysis of the variables was carried out (death cause, sex, age...), with the programme SPSS15.0. The total amount of deaths caused by tuberculosis was 217 (13,7%) and the specific mortality rate was 28,22 in 10,000 inhabitants. 54% (117) were males and 46% (100) females. We can conclude: 1. Tuberculosis was the first cause of death in El Puerto between 1923 and 1926. 2. The tuberculosis mortality standards are similar in the rest of the province of Cadiz. 3. It would be necessary to perform a deeper study to know whether the cause of the decrease in the mortality rate in 1926 was a consequence of an improvement in health and sanitary policies.